Ocupación del Suelo en el área urbana de la parroquia San Pedro de Vilcabamba, perteneciente al cantón y provincia de Loja - Torres Jaramillo, Carlos Efraín (2024)
The present degree project named “Land occupation in the urban area of the San Pedro de Vilcabamba parish, belonging to the canton and province of Loja" was initiated with the information provided by the Decentralized Autonomous Government of the Municipality of Loja, such as the DEM, Orthophoto, survey databases of the Land Use and Management Plan of 2020, from which the urban diagnosis was updated, verifying the information through field visits and the registration of data in technical data sheets, the aspects verified and updated in this point correspond to topography, slopes, wearing course, ecological protection and conservation areas, public spaces and green areas, public services, equipment, architectural and cultural heritage and current land use. With the information collected for the urban diagnosis and the elaboration of the maps the urban land of the parish was subclassified. This was done by cataloging the types of services and equipment in essential and complementary and also determining the degree of occupation that the land presents, with this information three types of land were obtained: consolidated urban land, unconsolidated urban land and protected urban land. The land occupation was established by digitizing the existing buildings in each of the properties, then the blocks were grouped by assigning them a code, this in order to calculate the block area and the built area in square meters, this data was used to calculate the built area, the level of land occupation and the vacant area, these calculations are made for each of the blocks, obtaining the corresponding level of occupation, finally it is reclassified based on this field, with which four ranges of land occupancy have been obtained: 0 - 25% which covers 20.41 hectares, 26% - 50% a total of 10.86 hectares, 51% - 75% an area of 3.74 hectares and the highest occupancy range of 76% - 100% which occupies a small area of 1.89 hectares, the highest ranges occupy the central area where housing has been consolidated which is why the percentage covered is small, on the other hand, the first three ranges have higher percentages because they are located in the larger sectors that make up the peripheral areas, where the buildings are dispersed and the blocks have not been fully consolidated. Key words: DEM, Orthophoto, urban diagnosis, land occupation, block.